Reformasi Fungsi Legislasi DPR Sebagai Upaya Penguatan Representasi Rakyat Dalam Mewujudkan Prinsip Demokrasi Deliberatif - Linda Listianingrum; Fakhris Lutfianto Hapsoro (PT Elaborium Elevasi Indonesia, 2026)
The House of Representatives (DPR) is a state institution with three functions: legislative, budgetary, and oversight, which constitutionally represent the people. However, in practice, these functions are often dominated by the interests of political parties supporting DPR members, resulting in disharmony in the implementation of DPR functions, particularly the legislative function, which frequently generates public controversy. This research employs a normative juridical method using statutory and conceptual approaches. The study examines the influence of political party intervention on legal products formed by the DPR, leading to the weakening of its position as a representative institution of the people. Therefore, constitutional reform of the DPR is necessary to ensure that the legislative function is carried out based on public interests without political party interference. This reform can be pursued by strengthening digital based public participation, adhering to fundamental principles of law making as stipulated in Law No. 13 of 2022 amending Law No. 12 of 2011, improving cadre development and recruitment of legislative camdidates through revisions tho the Election Law, and expanding the authority of the Constituional Court to ensure the legislative process complies with the principles of the rule of law within Indonesia’s contemporary constitutional and democratic governance framework system.